2020
DOI: 10.1186/s40658-020-00325-8
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a Bayesian penalized likelihood algorithm (Q.Clear) for 18F-NaF bone PET/CT images acquired over shorter durations using a custom-designed phantom

Abstract: Background The Bayesian penalized likelihood (BPL) algorithm Q.Clear (GE Healthcare) allows fully convergent iterative reconstruction that results in better image quality and quantitative accuracy, while limiting image noise. The present study aimed to optimize BPL reconstruction parameters for 18F-NaF PET/CT images and to determine the feasibility of 18F-NaF PET/CT image acquisition over shorter durations in clinical practice. Methods A custom-designed thoracic spine phantom consisting of several inserts, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…Our clinical data analysis also indicated significantly improved SNR, SBR, noise level and visual assessment scores in Q.Clear ( β = 400) than in OSEM + TOF, which was in line with previously published studies [ 11 14 ]. Compared to OSEM + TOF, Q.Clear can achieve a complete convergence and more accurate lesion quantitation, which will improve the SUVmax, SNR, SBR values of PET/MR in patients with suspected primary and metastatic torso cancers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our clinical data analysis also indicated significantly improved SNR, SBR, noise level and visual assessment scores in Q.Clear ( β = 400) than in OSEM + TOF, which was in line with previously published studies [ 11 14 ]. Compared to OSEM + TOF, Q.Clear can achieve a complete convergence and more accurate lesion quantitation, which will improve the SUVmax, SNR, SBR values of PET/MR in patients with suspected primary and metastatic torso cancers.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings were similar to previous studies on PET/MR using 68 Ga-prostate-specific membrane antigen (400–550) [ 1 ]. Previous studies on PET/CT suggested similar optimal β value of 350–400 ( 18 F-FDG) [ 12 , 15 , 16 ], 300–550 ( 18 F-fluciclovine) [ 17 ] and 300 ( 18 F-NaF) [ 14 ], 350 ( 68 Ga-labeled radiopharmaceuticals) [ 11 ], 400–550 ( 18 F-fluorocholine) [ 18 ]. While a few other studies of PET/CT suggested a higher β value of 500–750 [ 19 24 ], a study on the detection of sub-centimeter lesions suggested a β value of 200 [ 25 ].…”
Section: Discussionmentioning
confidence: 94%
“…The capability of BPL algorithm of shortening acquisition time was reported in several studies (16,17). A phantom and clinical study by Yang et al showed that TVREM could improve the lesion contrast and lower image noise of 68 Ga-PSMA-11 PET/CT compared to OSEM and enable a fast acquisition with 2 min/bed with preserved image quality (10).…”
Section: Discussionmentioning
confidence: 97%
“…Using BPL reconstruction in clinical studies enables improved lesion detection, and this has been shown in a wide variety of studies, for example, for 18 F-FDG in lung nodules [17,19], mediastinal nodes [20] and liver metastases [21]. PET imaging with other tracers also benefits from BPL reconstruction [17], for example, 68 Ga-PSMA [22,23], 68 Ga-DOTATOC [24], 68 Ga-RM2 [25], 90 Y-SIRT [26,27], 18 F-PSMA [28], 18 F-NaF [29], 68 Ga-citrate [30], 18 F-FACBC [31], 13 N-NH3 [32], 11 C-acetate [24] and 89 Zr-immuno-PET [33]. In addition, and perhaps most importantly, BPL is particularly advantageous in patients with high BMI [34,35], because they usually have the greatest background image noise where both the detection and quantification of small abnormalities are most problematic.…”
Section: The Use Of Bayesian Penalized Likelihood (Bpl) Reconstructionmentioning
confidence: 99%